Virtual Multimedia Communication for Physical Distancing in Physical Education. Issue 1 (February 2021) - Adi, S; Aldapit, Eki; Nova, Andi; Dharmika Nugraha, Pratama; Hutomo Bhakti, Yopi; Bang Redy Utama, Made
Abstract: Education is a sector that needs to go on to operate countinously as a means of student's activity and development in covid-19 pandemic. Multimedia is the best solution for managing PE class not to stop despite the social distancing issue. The aduance of technology in digitalization era isn't an obstacle to on going learning activities. Advance multimedia facility could surely be able to answer the problem arising in the society related to physical activity carried out as a form of learning. The efectiveness of multimedia learning can be seen from its trancendency to attract student's attention and interest as it combines the views, sound, and movement. So that learning takes place attractively and easily remembered by the students.